Latitude Effect on Carbon, Nitrogen and Oxygen Stable Isotope Ratios in Foliage and in Nitric-oxide Ions of Aerosols - Katsura, Hidemitsu (Asian Journal of Chemistry, 2012)
In this study, aerosol samples (PM 4.5) and foliage samples were collected in Singapore and in Fairbanks, Alaska in 2009 and 2010. Ion chromatography, gas chromatography-mass spectrometry and element mass spectrometry were used to measure anion concentrations and nitrogen and oxygen stable isotope ratios in nitrogen oxide ions of the aerosol samples, as well as to measure carbon and nitrogen stable isotope ratios in the foliage samples. In both Singapore and Fairbanks, it was observed that values of delta 15N/14N in nitric-oxide substances from aerosols were correlated with declination. The value of d 15N/14N in nitric-oxide substances from aerosols in Fairbanks increased with increasing declination due to more active conversions from 14N to 14C by neutron bombardment. This study implies that at least one of the reason of increasing concentration of carbon dioxide in the atmosphere past 2 centuries may be affecting by cosmicray bombardment to nitrogen in the atmosphere.